The Relationship Marketer Rethinking Strategic Relationship Marketing - Hougaard, Soren; Bjerre, Mogens (Springer Berlin Heidelberg : Imprint: Springer, 2009)
In "The Relationship Marketer", Søren Hougaard and Mogens Bjerre explain how the concept of the dyad (i.e., mutuality, or "you and me") is quickly becoming a fundamental principle in marketing. The authors suggest that understanding customer relationships, value co-creation, and customised business models in which effectiveness is evaluated on an individualised basis leads to outstanding business performance. Based on these principles the authors present a concrete and practically manageable framework for implementation. Readers will find surprising, useful, and applicable marketing models, typologies and tools, as well as guides to the systematic generation of strategic opportunities. "The Relationship Marketer" will be valuable reading for students and professionals in sales and marketing, as well as anyone seeking insights into dyadic market forces, which are moving industry beyond the outdated perspective of treating all customers equally.